Optimalisasi Kebutuhan Gizi Harian Anak Usia Dini di Era Ekonomi Berkelanjutan - Salsabila, Imtinan; Meisyari, Rinrin; Sumiati; Hartatu, Tiara (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
During early childhood growth and development, nutritional needs are very important to support emotional, cognitive and physical development. A balanced nutritional intake is needed to ensure optimal growth and development. However, in an era of sustainable economics, economic challenges such as high food prices or economic fluctuations can affect access to nutritious food for families with limited incomes. This research aims to provide a better understanding of the daily nutritional needs of young children. With this understanding, parents and caregivers can provide appropriate and balanced nutritional intake to support optimal growth and development of children. This research uses a bibliometric analysis method approach to measure information in scientific publications and literature relevant to the topic of early childhood nutritional needs. The research results show that poor nutrition in children can have a negative impact on children's growth and development and their ability to focus in dealing with problems and the surrounding environment. Providing nutrition to children must be based on the recommended doses and types of food appropriate to the child's age. The recommended contents of a dinner plate consist of rice, side dishes, natural products, vegetables and milk. This research provides a new contribution in optimizing the daily nutrition of early childhood by considering the family's economic background. Parents and caregivers are expected to provide appropriate and balanced nutritional intake despite economic limitations.